The effect of regulations on financial markets performance in Lesotho - Mohloki, Thabang (My University, 2021)
This paper unpacks the impact regulatory interventions on performance of the financial markets in Lesotho from 2009 to 2018 with the use of segmented regression analysis. The paper focuses on the impact of the 30% regulatory intervention imposed on insurance companies on performance of Lesotho financial systems. To ascertain financial markets performance, the study uses four measures of financial development being Broad Money; Liquid Liabilities of the Financial Sector; Outstanding Public Debt and Private Sector Credit as dependent variables. The study uses interrupted time series to evaluate dependant variables’ performance over time both prior and post the intervention. The study also assesses whether there are other determinants that may influence performance of financial markets. The findings demonstrate that the enforcement of the 30% local investment restriction had a positive impact on Broad Money; Liquid Liabilities of the Financial Sector and Outstanding Domestic Public Debt in Lesotho. The intervention did not however have an impact on Private Sector Credit. The findings further identifies Net International Reserves; Net Foreign Assets; Gross Domestic Product Growth; and Inflation as other determinants that significantly influence financial markets performance Lesotho.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Financial markets; Lesotho; Financial Sector; UCTD; SDG-8: Decent work and economic growth